Surface confinement of atomically thin Pt nanoclusters on 2D -MoN for durable pH-universal hydrogen evolution - Do, Viet-Hung (2023)
Engineering precious metals’ sub-nanometer cluster on 2D earth-abundant supports provides a promising approach for the development of high-efficient electrocatalysts in pursuit of green hydrogen. Herein, a novel solid phase deposition approach is demonstrated for the homogenous confinement of atomically thin Pt nanoclusters on 2D delta-MoN as a viable catalyst for pH-universal hydrogen evolution reaction. Notably, the optimized material (MoN-5% Pt) exhibits excellent catalytic performance as evidenced by low overpotentials required, excellent mass activity exceeding 20 A mgPt−1 at 100 mV overpotential, and outstanding stability with negligible activity degradation. The enhanced performance is attributed to (1) novel nanostructure, constituting atomically thin Pt nanoclusters confined on 2D δ-MoN substrate, thus rendering high atomic utilization and seamless surface mass transfer, and (2) influence of strong metal-support interaction that effectively limits structural deformation and performance degradation. Theoretical simulations reveal that the strong metal-support interaction induces substantial charge redistribution across the heterointerface, initiating an energy-favorable multi-active site microkinetics in which Pt atoms with an optimal hydrogen adsorption energy making way for enhanced H2 evolution, while Mo atoms situated at the heterointerface enhance water absorption/dissociation steps, enriching the catalytic surface with adsorbed hydrogen atoms.